Determination of consumer purchase thresholds for discoloration of beef steaks in retail display - Witberler, Stephanie Lynn (My University, 2025)
The objective of this study was to evaluate and determine similar purchasing tendencies and develop predictive models for consumer purchase likelihood based on objective measures of steak redness and discoloration to identify thresholds for consumer purchase of beef strip loin steaks. To accomplish this, the study was designed in two phases. Phase 1 required consumers to evaluate steak samples from various days of display ranging in discoloration from fresh to 100% discolored. Phase 2 required consumers to evaluated samples from all the same day of display with similar discoloration. Commercially packaged steaks were procured from a major beef processor in a case-ready format, identical to packages that would otherwise be displayed and sold at retail. Steaks were all the same USDA quality grade (upper 2/3 Choice), and were packaged and stored identically prior to the simulated retail display period. For each phase, steaks were removed from their mother-bag and placed in coffin-style retail cases and displayed under florescent lights for the pre-planned display period (0 – 14 days) in order to create differences in both steak color and discoloration. Consumers (N = 200 phase 1; 176 phase 2) evaluated steaks for overall appearance liking and identified whether or not they would purchase the product (yes/no) if it was fully-priced as well as if it was sold at a discount. Additionally, numerous objective color measures (L*, a*, b*, chroma, hue angle) were assessed on each sample and each was evaluated by a trained descriptive sensory panel for overall redness, % discoloration, and fat color. Results showed that in both phases of the study, all of the objective measures evaluated were predictors (P < 0.05) of consumer purchase intent. The predictive models accounted for 30 – 78% of the variation in consumer purchase intent for steaks sold at full-price and 27 – 72% of the variation when sold at a discount for Phase 1. In Phase 2, the models were less predictive, with models only accounting for 11 – 57% of the variation in consumer purchase likelihood in both full-priced and discounted samples. a* value and trained sensory panel discoloration scores were some of the best predictors evaluated. These models showed that even minimal discoloration has a large impact on consumer purchasing likelihood, with steaks that have 12 to 22 percent discoloration only having a 50% chance of being purchased at full-price. These results underscore the importance of insuring steaks sold at retail are maintained at a bright red level and free of discoloration, with the developed models proving some guidance to the requirements expected by consumers for purchase of beef steaks related to color characteristics.
Keywords: Beef; Meat color; Consumer; Discoloration; Retail; Sensory